Revitalisasi Keilmuan Fakultas Ushuluddin Menghadapi Tantangan Peradaban Global - Nasihun Amin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Abstract: The wave of information and communication appear to cause global clash  of civilization. This seriously challenges religion because morality lies as the basic  problem. Concerning this issue, Ushuluddin faculty, that produces religious scholars,  has a strategic position in responding to this situation. As an academic institution,  Ushuluddin faculty has to do self-reformulation and revitalization in order to respond  the global challenge. It does not only focus on producing scholars that are excellent in  understanding religious studies (substantial skill). But, it has also to equip them with  great skill on technicality, practicalities as well as relational skill. These expertise and  skills will give them authority to direct morality in this global civilization.  Abstrak: Adanya gelombang informasi dan komunikasi ternyata membawa dampak  benturan peradaban pada skala global. Pada keadaan demikian, agama mendapat  tantangan yang luar biasa berat karena inti persoalannya adalah pada moral. Dalam  konteks ini, peran Fakultas Ushuluddin (FU) sebagai pencetak ahli agama sebagai  bagian penting dalam institusi agama, mempunyai posisi yang strategis. Karenanya,  tuntutan yang harus segera dilakukan adalah bagaimana FU melakukan reformulasi  dan revitalisasi dalam dirinya untuk menjawab tantangan global tersebut. Melalui  penguasaan dan pemahaman agama yang baik dan tepat (substantial skill), yang  didukung kecakapan teknis (technical skill) tertentu dan kecakapan relasional  (relational skill), maka mereka akan memiliki wibawa moral untuk memberikan arah  moral dalam peradaban global.